2011
DOI: 10.1371/journal.pone.0022569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transposable Elements in Neural Tissues during Xenopus Development

Abstract: Transposable elements comprise a large proportion of animal genomes. Transposons can have detrimental effects on genome stability but also offer positive roles for genome evolution and gene expression regulation. Proper balance of the positive and deleterious effects of transposons is crucial for cell homeostasis and requires a mechanism that tightly regulates their expression. Herein we describe the expression of DNA transposons of the Tc1/mariner superfamily during Xenopus development. Sense and antisense tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…For example, one remarkable study recently identified thousands of reintegration sites for LINE-1 (L1), Alu and composite SVA (SINE, VNTR and Alu ) elements in the human caudate and hippocampus 68 . These findings are consistent with previous reports suggesting that retrotransposon activity is important for neural development and plasticity 6971 . In addition, they also indicate that retrotransposon-derived ncRNAs and ncRNAs that are responsible for regulating retrotransposition events (via endo-siRNAs and piRNAs) mediate in neurons and act as regulatory control systems for the establishment, maintenance and plasticity of the transcriptional architecture of the brain.…”
Section: Neural Development Maintenance and Plasticitysupporting
confidence: 94%
“…For example, one remarkable study recently identified thousands of reintegration sites for LINE-1 (L1), Alu and composite SVA (SINE, VNTR and Alu ) elements in the human caudate and hippocampus 68 . These findings are consistent with previous reports suggesting that retrotransposon activity is important for neural development and plasticity 6971 . In addition, they also indicate that retrotransposon-derived ncRNAs and ncRNAs that are responsible for regulating retrotransposition events (via endo-siRNAs and piRNAs) mediate in neurons and act as regulatory control systems for the establishment, maintenance and plasticity of the transcriptional architecture of the brain.…”
Section: Neural Development Maintenance and Plasticitysupporting
confidence: 94%
“…Faunes et al (9) reported different expression profiles of Tc1 family transposons in the nervous system of Xenopus tropicalis. the importance of the developmental regulation in the expression of the transposons in the corn plant was shown by li et al (17).…”
Section: Sequence Resultsmentioning
confidence: 99%
“…We extended these observations by showing that a DNA transposable element of the Tc 1/ mariner family is differentially expressed during X. tropicalis development 8 , 9 . The general structure of Tc 1/ mariner elements is shown in Figure 1A.…”
Section: Expression Of Transposable Elements From the Tc1/mariner Fammentioning
confidence: 53%